The Free Nutritious Meal Program In Indonesia: A Systematic Review Of Food And Nutrition Perspectives - viozani, Ramadhanti; Yulastri, Asmar (Universitas Negeri Padang, 2025)
This study aims to synthesize scientific evidence on food quality, children's nutritional status, and the sustainability of nutrition interventions in Indonesia using a systematic literature review approach. A total of 11 national and international articles published between 2019 and 2025 were selected based on relevance to child nutrition programs and the availability of empirical data on food quality, determinants of nutritional status, and local food innovations. The data were analyzed thematically to identify key findings and implementation gaps. The results indicate that spatial disparities and socio-economic factors, particularly maternal education, sanitation access, and household purchasing power, are major determinants influencing children's nutritional status. In addition, local resource–based food innovations, such as locally produced therapeutic foods and nutrient-dense local ingredients, show strong potential to improve dietary quality and support the sustainability of nutrition programs. Therefore, the implementation of the Free Nutritious Meal Program should be supported by evidence-based food quality standards, strengthening of local food systems, and adaptive intervention strategies to achieve long-term improvements in children's nutritional status in Indonesia.